SOME CHARACTERISTICS OF CROATIAN ELITE ATHLETES - BABIĆ Vesna; BJELIĆ G.; BOSNAR K. (Editura Universitatii Transilvania din Brasov, 2019)
The aim of this paper was to discover certain characteristics of top athletes for a better understanding of their career, life and function, and to rid oneself of widespread prejudices and stereotypes about athletes. The sample encompassed 301 athletes (154 F and 147 M), medal winners in top competitions: the Olympic Games, World and European Championships, World Cups and European Cups, and the Mediterranean Games from 1992 to 2012. The participants in the survey were those athletes who were available and who willingly joint the survey, including athletes from 39 sports (22 Olympic, 15 non-Olympic and 2 associated). The answers to 27 questions, out of the total of 81 from the questionnaire used in the doctoral thesis by G. Bjelić, Ph.D. (2018), were analysed. Research has shown that athletes are unhappy with the support by the state, the alliance and/or their club. Most believe that they received too little support and have invested in sports more than their sport has given to them. What attracts them most is success, socializing and travelling, and gaining discipline, working habits and organizational skills. Most of them are also attracted by great efforts and sacrifices. As for public exposure, most respondents are indifferent. Yet, double is the number of those deterred by it than those attracted by it. What deters athletes from sport is mostly neglecting other activities and a lack of time for socializing and entertainment outside sports. It was further determined that most athletes are satisfied with themselves as persons.